Analysis of Fecal Microbiome and Metabolome Changes in Goats When Consuming a Lower-Protein Diet with Varying Energy Levels - Hu Liu; Anmiao Chen; Wenji Wang; Weishi Peng; Kaiyu Mao; Yuanting Yang; Qun Wu; Meng Zeng; Ke Wang; Jiancheng Han; Hanlin Zhou (Microorganisms)
The objective of this study was to evaluate the effect of fecal bacterial community and metabolomics in goats when consuming a lower-protein diet with different energy levels. Eight healthy Leizhou goats, with 11 ± 0.78 kg of body weight, were selected and housed individually in cages. The animals were randomly allocated to a lower-protein diet that varied with four metabolites energy levels (7.01, 8.33, 9.66, and 10.98 MJ/kg DM) in a replicated 4 × 4 Latin square design. Notably, energy-dependent microbial restructuring was observed at both phylum and genus levels. At the phylum level, the relative abundances of Firmicutes and Spirochaetote increased linearly, whereas the Bacteroidota and Patescibacteria decreased linearly with increasing dietary energy levels (p < 0.05). The relative abundances of Verrucomicrobiota increased quadratically, whereas others decreased quadratically with increasing dietary energy levels (p < 0.05). At the genus level, a total of 316 bacteria were identified in the 32 fecal samples. The relative abundances of Christensenellaceae_R-7_group, unclassified_f__Lachnospiraceae, Ruminococcus, norank_o__Clostridia_UCG-014, Treponema, [Eubacterium]_siraeum_group, and [Eubacterium]_ruminantium_group increased linearly, whereas the Oscillospiraceae_UCG-005, norank_f__[Eubacterium]_coprostanoligenes_group, Prevotellaceae_UCG-004, unclassified_c__Clostridia, norank_f__Ruminococcaceae, unclassified_f__ Oscillospiraceae, and others decreased linearly with an increasing dietary energy levels (p < 0.05). In addition, the metabolomic analysis of feces showed that there are many differential metabolites in goats when consuming a lower-protein diet with different energy levels; for example, lipid metabolism and amino acid metabolic pathways were increased in MLE, MHE, and HE groups compared to the LE group. In conclusion, this study provides further information regarding the effects on fecal bacterial community composition and metabolites in goats when consuming a lower-protein diet with different energy levels.